Reproduction of Ophioplocus januarii (Echinodermata: Ophiuroidea): a continuous breeder in northern Patagonia, Argentina - Brogger, Martin Ignacio (2013)
We studied the reproduction of Ophioplocus januarii from Playa Villarino (42° 24 S, 64° 17 W), based on monthly samples collected between April 2005 and April 2007. Gonad indices were generally synchronous for males and females with little seasonal pattern. The changes of the gonad index were not significantly correlated with day length or water temperature. Histological analyses showed no evidence of seasonal differences in the maturation stages of the gonads, but that ovaries contained oocytes at different stages of development during the year. Thus, variations in the gonad index resulted from differences in the number of gametes in the gonads each month, suggesting that there are some periods when spawning intensity is higher than in others. Oocyte size frequency analysis revealed only slight accumulation of large oocytes, with the largest oocytes over 400 μm in diameter. This, together with the absence of oocytes being resorbed, suggests that gametes are being released continuously without a defined resting phase for the ovary. O. januarii breeds continuously, differing from the seasonal pattern of many other invertebrates living in shallow waters off the Patagonian coast as well as in other temperate seas, providing helpful information towards a better understanding of reproduction in Ophiuroidea.